From detached to alarmed: How eco-emotion profiles predict concern and sacrifice for the planet. - Andreas K Jäger; Donald W Hine (PLoS ONE)
The rapid degradation of the environment is one of our greatest challenges in the 21st century. To avoid the worst consequences, human behavior change is required. The current study investigated how feelings about environmental problems (eco-emotions) predict concern for the natural environment and willingness to make sacrifices for it. Using a cross-sectional online sample of 286 New Zealand residents, latent profile analysis identified three profile groups with distinct patterns of eco-emotions: emotionally-detached (40%), emotionally-ambivalent (34%), and empathic-alarmed (26%). Validation analyses revealed that members of the empathic-alarmed segment reported significantly higher levels of environmental concern and willingness to make sacrifices for the environment than members of the emotionally-ambivalent segment, who in turn expressed greater concern and willingness to sacrifice than members of the emotionally-detached segment. Findings from this study suggest that inducing a combination of negative eco-emotions with compassion may be effective for promoting environmental concern and pro-environmental sacrifice.